2014
DOI: 10.1063/1.4887367
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ion insertion study into a nanostructured vanadium oxide in aqueous salt solutions

Abstract: Articles you may be interested inThermal stability and the magnetic properties of hybrid vanadium oxide-tetradecylamine nanotubes J. Appl. Phys. 112, 053912 (2012); 10.1063/1.4749417 Ion sensitivity of the flowerlike ZnO nanorods synthesized by the hydrothermal process

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The single crystals of GaAsO 4 ·2H 2 O employed in this study were a minor product from the hydrothermal preparation of vanadium oxide nanostructures . In summary, an aqueous solution of hydrolyzed VCl 4 , Na 2 HAsO 4 ·7H 2 O, GaCl 3 , and guanidinium hydrochloride, in a mole ratio of 252:1:3.75:5.78, was placed in a Parr bomb and heated at 456 K for 90 h before being cooled to room temperature.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The single crystals of GaAsO 4 ·2H 2 O employed in this study were a minor product from the hydrothermal preparation of vanadium oxide nanostructures . In summary, an aqueous solution of hydrolyzed VCl 4 , Na 2 HAsO 4 ·7H 2 O, GaCl 3 , and guanidinium hydrochloride, in a mole ratio of 252:1:3.75:5.78, was placed in a Parr bomb and heated at 456 K for 90 h before being cooled to room temperature.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…vanadium oxide nanostructures. 7 In summary, an aqueous solution of hydrolyzed VCl 4 , Na 2 HAsO 4 ·7H 2 O, GaCl 3 , and guanidinium hydrochloride, in a mole ratio of 252:1:3.75:5.78, was placed in a Parr bomb and heated at 456 K for 90 h before being cooled to room temperature. Perfect colorless octahedral crystals of GaAsO 4 ·2H 2 O were hand-separated from the vanadium oxide nanosheets that are the major product of this reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For this purpose, many materials that are able to reversibly incorporate NH 4 + into their lattice hosts have been proposed and demonstrated, such as Prussian blue analogs (PBAs), MnO 2 , , MoO 3 , and vanadium-based materials. Of all the explored electrode materials, PBAs have drawn much attention because of their advantages (facile preparation, stable structure, good cyclability, fast kinetics, and almost negligible volume variation upon cycling), and almost all the pioneering works from 2012 to 2020 have focused on the electrochemical performance of PBAs in ammonium salt solutions. However, many PBAs used as electrode materials in various batteries exhibit a weird initial Coulombic efficiency (above 100%). For example, Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, electrode materials for aqueous sodium ion batteries are being explored, such as V 2 O 5 15 and Na 3 Ti 2 (PO 4 ) 3 . 16,17 However, to the best of our knowledge, the use of anatase nanotube in aqueous sodium batteries has not been reported in the literature.…”
mentioning
confidence: 99%
“…10,11 We very recently have reported sodium batteries using anatase nt-TiO 2 with very good electrochemical behavior: areal capacity in the order of 1.0-1.5 mAh/cm 2 , and after 600 discharge-charge cycles the gravimetric capacity is about 200 mAh/g. 12 The use of aqueous electrolyte batteries may be an alternative to lithium 3,13 and sodium [14][15][16][17] ion batteries which use organic solvents, with safety, cost and environmental advantages. Thus, in a pioneering work, Li et al reported that the aqueous lithium ion batteries compete with nickel-cadmium and lead-acid batteries on the basis of stored energy per unit of weigh.…”
mentioning
confidence: 99%